2019
DOI: 10.1038/s41598-019-40813-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the bioavailability of benzo[a]pyrene (B[a]P) in a B[a]P-contaminated soil using the different addition approaches

Abstract: Determination of the bioavailability of the hydrophobic organic contaminant benzo[a]pyrene (B[a]P) is extremely important for assessing its environmental risk. The effect of addition manner of B[a]P on the bioavailability and toxicity of B[a]P in soil remains unclear. In this study, soil samples, spiked with B[a]P by one-time or multiple-time additions, were tested to investigate the available fraction of B[a]P in soils, the uptake of B[a]P by red wiggler worms ( Eisenia fetida ), as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Alterations in ROS-scavenging enzymes and oxidative stress levels have also been reported. Duan et al [164] found changes in ROS-scavenging enzymes (superoxide dismutase and catalase) in E. fetida after 14 days of exposure to benzo-[a]pyrene, but not lipid peroxidation at concentrations below 500 mg kg À1 d.w. For the same species and chemical, Ye et al [168] denoted an increase in superoxide dismutase and peroxidase activities and failure to reach a new homeostasis status after 56 days at 10 mg kg À1 d.w. Glutathione S-transferases alterations were reported for phenanthrene and fluorene in E. fetida [169]. Recent OMICS have highlighted important differences in toxicity pathways elicited by PACs to soil organisms, as shown by Roelofs et al [170] for F. candida and E. crypticus after exposure to phenanthrene.…”
Section: Effect Of Polycyclic Aromatic Compounds At Sub-organism Levelmentioning
confidence: 99%
“…Alterations in ROS-scavenging enzymes and oxidative stress levels have also been reported. Duan et al [164] found changes in ROS-scavenging enzymes (superoxide dismutase and catalase) in E. fetida after 14 days of exposure to benzo-[a]pyrene, but not lipid peroxidation at concentrations below 500 mg kg À1 d.w. For the same species and chemical, Ye et al [168] denoted an increase in superoxide dismutase and peroxidase activities and failure to reach a new homeostasis status after 56 days at 10 mg kg À1 d.w. Glutathione S-transferases alterations were reported for phenanthrene and fluorene in E. fetida [169]. Recent OMICS have highlighted important differences in toxicity pathways elicited by PACs to soil organisms, as shown by Roelofs et al [170] for F. candida and E. crypticus after exposure to phenanthrene.…”
Section: Effect Of Polycyclic Aromatic Compounds At Sub-organism Levelmentioning
confidence: 99%
“…Reports also showed that the increased pH and EC in sandy soil and aging in clayey soil caused > 55 % and > 85 % of the changes in B(a)P extractability, respectively (Meng et al, 2019; Zhou et al, 2021). It has been found that the addition method (one‐time or multiple‐time addition) could affect the bioavailability of B(a)P in soils, its uptake by earthworms, as well as the enzyme activities in earthworm coelomocytes, due to the B(a)P age in soil (Ye et al, 2019). With the accumulation of B(a)P in receptors, varying degrees of damage were observed, such as the ultrastructural damage in spring barley tissues depending on concentrations (Fedorenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is the bioavailable fraction, rather than the total contaminant in soils, that is critical for defining exposure, uptake and the consequent risk to the environmental receptors, and could be used to assess the effectiveness or feasibility of bioremediation technologies (Li et al, 2013). Many researchers have observed an 'ageing effect' of hydrophobic organic contaminants (HOCs), such as PAHs in soil (Duan et al, 2015;Meng and Chi, 2017;Ye et al, 2019). Such process are often determined by increased sorption or decreased desorption which are controlled by several factors including soil properties (e.g.…”
Section: Introductionmentioning
confidence: 99%